2013
DOI: 10.1177/016146811311500309
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Successful Online Teaching in Higher Education: Voices of Exemplary Online Teachers

Abstract: Background Although advances in distance learning have shown signs of a reconfiguration of the teacher's role in online environments, a large number of online teaching practices still do not show many signs of this shift. Given the need for a change in pedagogies, investigating how exemplary teachers transfer their thinking, pedagogical knowledge, and beliefs to successful online teaching is critical to understanding new online learning and teaching practices. The research on online teacher roles and practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 34 publications
1
59
0
1
Order By: Relevance
“…This is not surprising because online learning exists in a significantly different context. Baran et al (2013) stated that the vital roles and competencies expected by online teachers often clashed in the literature, and they depended on the online teaching context. Thus, the unpredictable learning environment necessitates educators to possess various competencies.…”
Section: Online Teaching Competenciesmentioning
confidence: 99%
“…This is not surprising because online learning exists in a significantly different context. Baran et al (2013) stated that the vital roles and competencies expected by online teachers often clashed in the literature, and they depended on the online teaching context. Thus, the unpredictable learning environment necessitates educators to possess various competencies.…”
Section: Online Teaching Competenciesmentioning
confidence: 99%
“…Besides that, faculty needs to interact with support personnel and colleagues for assistance and guidance to address the issues encountered in teaching online. Previous studies have shown the contribution of collegial learning groups to faculty’s adaption to online teaching (Baran et al, 2013 ; Samarawickrema & Stacey, 2007 ). Moreover, it is necessary to set up a collaborative professional community to cultivate a shared vision among online faculty.…”
Section: Bibliometric Analysis Of Literature: Discussionmentioning
confidence: 99%
“…The tension fields “time pressure” and “support” could also be linked to one another since the participants indicated that they cannot make optimal use of the provided professional support due to a lack of time. Lack of time is an often-heard problem for teachers, for example, Baran et al [ 3 , p. 5] already stated before COVID-19 that “the process of adapting to online teaching environments also requires a time investment on the part of the teachers concerning the design and development of learning resources.” Finally, most of the participants positively evaluated the flexibility in time and space of online learning materials but saw pitfalls for students who are unable to manage their own time, which is in line with Bettinger et al [5] who acknowledged the students’ challenge to manage their (online) time. Yet, the results in this study refine the flexibility in time and space between first-year bachelor students who need more attention to digitally connect and more experienced master students who have better self-regulating skills.…”
Section: Discussionmentioning
confidence: 99%